2009
DOI: 10.4161/cbt.8.4.7332
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced CCR7 expression via HIF-1α and HIF-2α correlates with migration and invasion in lung cancer cells

Abstract: Hypoxia, a common phenomenon in human solid tumors, is associated with invasion and metastasis in various tumors. Hypoxia inducible factors (HIFs) are key molecules in the hypoxic response, and regulate the activation of specific genes, which mediate many of the adaptations to hypoxia. CC chemokine receptor 7 (CCR7) has been shown to play a critical role in cell chemotaxis and homing, which are key steps in cancer metastasis. A study has demonstrated that hypoxia could upregulate CCR7 in breast cancer cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 21 publications
(30 reference statements)
5
59
0
Order By: Relevance
“…This result was consistent with previous reports on HIF-1α and HIF-2α expression in lung cancer. 13 We hypothesized that HIF-1α and HIF-2α together were involved in the migration and invasion of gastric cancer. To test this hypothesis, we examined HIF-1α and HIF-2α in the gastric cancer cell line SGC7901 under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with previous reports on HIF-1α and HIF-2α expression in lung cancer. 13 We hypothesized that HIF-1α and HIF-2α together were involved in the migration and invasion of gastric cancer. To test this hypothesis, we examined HIF-1α and HIF-2α in the gastric cancer cell line SGC7901 under hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In one study the authors suggest that CCR7 enhances metastasis by upregulating MMP-9 expression [59]. Li et al showed that hypoxia may induce CCR7 expression on tumor cells to stimulate migration and invasion of lung cancer cells, using the HIF1α and HIF2α pathway [60]. …”
Section: Cytokines and Growth Factors Control Lymphangiogenesismentioning
confidence: 99%
“…Binding to CCRL1 results in internalization and degradation of these ligands (Comerford et al 2006), which attenuates the immune response (Heinzel et al 2007). Recent reports have shown that the CCRL1 ligands promote proliferation and prevent apoptosis (Wang et al 2005; Li et al 2009; Shen et al 2009; Johnson et al 2010; Xu et al 2011, 2012), suggesting that increased expression of Ccrl1 may reduce tumor response through chemokine depletion. This idea is further supported by the observation of a significantly higher rate of tumor growth in wild-type BALB/c mice compared to plt mice, which lack CCL19 and CCL21, implanted with a syngeneic squamous cell carcinoma cell line (Mburu et al 2006).…”
Section: Discussionmentioning
confidence: 99%